(untitled) (Research, Society and Development, 2021)
Autism spectrum disorder (ASD) is characterized by deficits in communication, language, and restricted and repetitive behavior patterns. The frequency of individuals diagnosed with ASD has increased over the past few years, and consequently leads to a greater demand for patients in dental offices. This increased demand makes the dental surgeon need knowledge about the particularities of the patient with ASD, associated comorbidities and more common oral pathologies, in order to carry out an effective therapeutic approach and restore the patient’s health. Thus, this study aimed to carry out a literature review on the importance of dental treatment in patients with autism spectrum disorder through the analysis of the most common oral affections in these individuals, as well as the challenges faced by the dentist in the face of all. complexity of the TEA. As a methodology for the study, a search was performed for the keywords autism, dentistry, oral health and pediatric dentistry in the Lilacs, Pubmed and Scielo databases. Conclusion: given the numerous difficulties encountered by parents and caregivers, patients with autism spectrum disorder must receive an interdisciplinary treatment, where the dentist belonging to this team must convey the importance of preventive care in relation to oral pathologies and guidelines regarding diet and oral hygiene, as well as proper treatment.